KEKUATAN PENGALAMAN KONSUMEN DAN KEPERCAYAAN TERHADAP MINAT BELI ULANG PADA TOKO HANDMADE ADDICTIVE - pebrila, lisa; Ramdan, Asep M.; Samsudin, Acep (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.08.NO.04.TAHUN 2019, 2019)
The purpose of this study was to measure the interests of consumers and interest in the interest of repurchasing consumers of Handmade Addictive Cibatu Sukabumi Regency. The method used in this study uses a sampling method that is included in the method of random sampling by distributing 157 questionnaires consumers. The analysis technique used is multiple linear regression analysis techniques, including test coefficient of determination, multiple correlation coefficient, simultaneous test (F test), and partial test (t test). The results of the test coefficient of determination seen from the value (adjusted R2) of 0.980 can be interpreted as the experience of Consumer Experience and Trust in the interest of repurchase is 98.0%. The remaining 0.02% was not approved by other studies. Based on multiple coefficient trials seen from the R value of 0.990, shows a very strong real relationship between consumer experience and trust with repurchasing interest. Based on the F test the probability value sig. 0.00 <0.05 which means together Consumer Experience (X1) and Trust (X2) significant confidence in Repurchase Interests (Y). Based on the t test showing Consumer Experience (X1) has a significant effect on Repurchase Interest (Y), Trust (X2) has a significant effect on Repurchase Interest (Y).